TARI PIRIANG BATOGHANG DI NAGARI KOTO BARU KECAMATAN KOTO BARU KABUPATEN DHARMASRAYA DITINJAU DARI ASPEK KOREOGRAFI - Indah Fajar Wati; Herlinda Mansyur; Nerosti Nerosti (FBS Universitas Negeri Padang, 2018)
AbstractThis article aims to reveal and describe the choreography of Piriang Batoghang dance in the dance class of Kajang Lako, Nagari Koto Baru Dharmasraya regency. This research was qualitative research with descriptive method. The object of this research was Piriang Batoghang dance in the dance class of Kajang Lako, Nagari Koto Baru, Dharmasraya regency. The instrument in this study was the researcher itself, and the types of data were primary and secondary data. The technique of data collection was done by documents study, observation, interview and documentation. The results showed that the form of the choreography of Piriang Batoghang dance was in the form of group choreography pattern and it used composition of large groups. This was a kind of dance that prioritized cooperation and raised the idea of Koto Baru’s community who generally work as farmers and solid when they work. Piriang Batoghang dance used floor patterns, the design of straight and curved lines. Piriang Batoghang dance has 10 top designs namely flat, within, vertical, horizontal, contrast, pure, static, straight, curved, and angles designs. The dance costumes were inspired from daily costume of society who goes to rice fields to harvest rice which have been modified. Keywords: Piriang Batoghang Dance